DESIGN AND DEVELOPMENT OF GRAPHIC DESIGN IN THE FORM E-KATALOG ON AS CELLULAR - Jimmy Pratama; Hut Kemri Marsudi (Universitas Internasional Batam, 2022)
This community service program has the aim of increasing sales, reaching a wider range sales market, and allowing new customer entrants via promotion through digital media given e-catalogue. With the globalized era and progressive rate in technology has led citizens to be active in using the internet. Partners in community service are the As Cellular engaging in an online shop of the smartphone business located in Orchard Park Cluster Citrus 3 No.08, Batam, Kepulauan Riau. The method used to compile data is through interview and observation. The results of the interviews and observations will be summarized in the form of documents so that they can be used as memos in making and implementing the system to be carried out.